2014
DOI: 10.1016/j.chiabu.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A two-center retrospective review of the hematologic evaluation and laboratory abnormalities in suspected victims of non-accidental injury

Abstract: Investigation for bleeding disorders in the context of suspected non-accidental injury (NAI) is inconsistent. We reviewed the hematologic evaluation of children who presented with symptoms of bleeding and/or bruising suspicious for NAI to determine the frequency of hematologic tests, abnormal hematologic laboratory results, and hematologic diagnoses. A retrospective cohort study design was employed at two freestanding academic children’s hospitals. ICD-9 codes for NAI were used to identify 427 evaluable patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Prolongation of the PT has been documented as a consequence of traumatic brain injury, attributable to parenchymal brain damage 32,33 . A retrospective study in victims of suspected non‐accidental injury showed high incidence of prolonged PT and APTT of 22.5% and 17.4% respectively, at presentation 26 …”
Section: Interpreting the Results Of Haematological Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolongation of the PT has been documented as a consequence of traumatic brain injury, attributable to parenchymal brain damage 32,33 . A retrospective study in victims of suspected non‐accidental injury showed high incidence of prolonged PT and APTT of 22.5% and 17.4% respectively, at presentation 26 …”
Section: Interpreting the Results Of Haematological Testingmentioning
confidence: 99%
“…32,33 A retrospective study in victims of suspected non-accidental injury showed high incidence of prolonged PT and APTT of 22.5% and 17.4% respectively, at presentation. 26 In VKDB, the PT is prolonged and levels of the vitamin K-dependent factors (II, VII, IX and X) are reduced, sometimes accompanied by a prolonged APTT. Correction by administration of oral or parenteral vitamin K, with or without plasma, results in normalisation of the coagulopathy.…”
Section: Transient Abnormalities Of Blood Coagulation Testsmentioning
confidence: 99%
“…Coagulopathy can reflect the severity of injury rather than its location . Prolonged laboratory values of prothrombin time and aPTT have been reported in trauma series . The main factors to initial acute trauma coagulopathy are tissue trauma, hypoperfusion, inflammation, and sympatho‐adrenal activation leading to hemostatic abnormalities such as hypocoagulability, fibrinolysis, and endothelial hyperpermeability .…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory testing on trauma patients generally includes evaluation of hematological profiles and blood chemistries including sodium, potassium, chloride, blood urea nitrogen, creatinine, glucose, and amylase levels . In addition, clotting profiles are usually obtained for these patients . In the literature, there are few studies that have evaluated possible alterations in laboratory tests in patients with maxillofacial fractures …”
Section: Introductionmentioning
confidence: 99%
“…Rare metabolic disorders that are associated with subdural hemorrhages, such as glutaric aciduria type 1, are diagnosed by characteristic neurologic lesions, urine abnormalities, and other screening tests. 102 Some clinicians may worry that clinical findings suspicious for child abuse may actually be manifestations of a medical disease, such as Ehlers Danlos syndrome, 103 Kasabach-Merritt syndrome, 104 coagulopathy, 105 infection, 106 non-intentional brain trauma, 107 or cardiopulmonary resuscitation. 12 …”
Section: Controversy In “Diagnosing” Child Abusementioning
confidence: 99%